A population-based study on the association between educational length, prostate-specific antigen testing and use of prostate biopsies. (3rd March 2016) - Nordström, Tobias; Bratt, Ola; Örtegren, Joakim; Aly, Markus; Adolfsson, Jan; Grönberg, Henrik
Abstract: Objective. The aim of this study was to determine whether educational length affects prostate-specific antigen (PSA) testing and the time to prostate biopsy for men with raised PSA values. Materials and methods. Using register data on all men in Stockholm County in 2013 ( n  = 1, 052, 841), the limited-duration point prevalence of PSA testing and time between test and prostate biopsy or repeat testing were analysed. Patterns of follow-up were assessed using Kaplan–Meier product limit estimators and Cox proportional hazard models. Educational length was categorized as short (≤9 years), intermediate (10–12 years) or long (≥13 years). Results. PSA testing increased with educational length in all age groups. Among men aged 50–69 years, 61% with long and 54% with short education had had a PSA test within the preceding 10 years ( p  < 0.001). In men with PSA 4–10 ng/ml, 40% [95% confidence interval (CI) 38–41] with long and 27% (95% CI 26–29) with short education underwent a prostate biopsy within 12 months. After adjusting for PSA level and age, educational length was still associated with the chance of having a prostate biopsy in men with PSA 4–10 ng/ml (hazard ratio 1.22, 95% CI 1.12–1.31), but not in men with higher PSA values. Conclusion. PSA testing increased with educational length. Men with long education were more likely to have a prostate biopsy after an increased PSA value below 10 ng/ml than men with short education. These differences may contribute to the worse prostate cancer outcomes observed among men with lower socioeconomic status.